EVALUATION OF THE EFFECTS OF COMBINING DIFFERENT SIGNAL PRIORITY RULES AND BUS OPERATION AT THE SIGNALIZED INTERSECTION - Okamura, Toshiyuki; Pradeep, Kumar Shrestha; Nakamura, Fumihiko (INFRASTRUCTURE PLANNING REVIEW, 2008)
Bus signal priority (BSP) effects on bus and other vehicles varies for different combinations of conditional BSP rules, infrastructures and bus stop operations under different demand. This paper analyzes four cases of conditional BSP for given bus stop operation and bus lane with varying demand using CORSIM. BSP rules considered are long vehicle detection, identifying regular bus, amount of schedule delay, door closing time. The impacts are evaluated for two objective functions i.e travel time for priority and nonpriority direction. The method will be beneficial to find combination of strategies with benefit to bus and acceptable disbenefit to non-priority direction.